Diagnosis, Therapy and Follow-up of Vaginal Cancer and Its Precursors. Guideline of the DGGG and the DKG (S2k-Level, AWMF Registry No. 032/042, October 2018) - Schnürch, Hans-Georg; Ackermann, Sven; Alt-Radtke, Celine D.; Angleitner, Lukas; Barinoff, Jana; Beckmann, Matthias W.; Böing, Carsten; Dannecker, Christian; Fehm, Tanja; Gaase, Rüdiger; Gass, Paul; Gebhardt, Marion; Gieseking, Friederike; Günthert, Andreas; Hack, Carolin C.; Hantschmann, Peer; Horn, Lars Christian; Koch, Martin C.; Letsch, Anne; Mallmann, Peter; Mangold, Bernhard; Marnitz, Simone; Mehlhorn, Grit; Paradies, Kerstin; Reinhardt, Michael J.; Tholen, Reina; Torsten, Uwe; Weikel, Wolfgang; Wölber, Linn; Hampl, Monika (Geburtshilfe und Frauenheilkunde, 2019)
Purpose This is an official guideline, published and coordinated by the Gynecological Oncology Working Group (AGO) of the German Cancer Society (DKG) and the German Society for Gynecology and Obstetrics (DGGG). Vaginal cancers are rare tumors, which is why there is very little evidence on these tumors. Knowledge about the optimal clinical management is limited. This first German S2k guideline on vaginal cancer has aimed to compile the most current expert knowledge and offer new recommendations on the appropriate treatment as well as providing pointers about individually adapted therapies with lower morbidity rates than were previously generally available. The purpose of this guideline is also to set up a register to record data on treatment data and the course of disease as a means of obtaining evidence in future.Methods The present S2k guideline was developed by members of the Vulvar und Vaginal Tumors Commission of the AGO in an independently moderated, structured, formal consensus process and the contents were agreed with the mandate holders of the participating scientific societies and organizations.Recommendations To optimize the daily care of patients with vaginal cancer: 1. Monitor the spread pattern; 2. Follow the step-by-step diagnostic workup based on initial stage at detection; 3. As part of individualized clinical therapeutic management of vaginal cancer, follow the sentinel lymph node protocol described here, where possible; 4. Participate in the register study on vaginal cancer.Ziel Offizielle Leitlinie, publiziert und koordiniert von der Arbeitsgemeinschaft Gynäkologische Onkologie (AGO) in der Deutschen Krebsgesellschaft (DKG) und der Deutschen Gesellschaft für Gynäkologie und Geburtshilfe (DGGG). Vaginalkarzinome gehören zu den seltenen Tumoren, dadurch fehlen bisher Evidenzen. Kenntnisse über das optimale klinische Management sind gering. Diese erste deutsche S2k-Leitlinie zum Vaginalkarzinom soll das aktuelle Expertenwissen zusammentragen und neue Behandlungsempfehlungen anbieten, um eine individuell angepasste Therapie mit geringerer Morbidität als bisher zu ermöglichen. Zur zukünftigen Gewinnung von Evidenzen soll eine Registerstelle für die Behandlungsdaten und Krankheitsverläufe eingerichtet werden.Methoden Die vorliegende S2k-Leitlinie wurde von den Mitgliedern der Kommission Vulva- und Vaginaltumoren der AGO entworfen, in einem unabhängig moderierten formalen Konsensusverfahren strukturiert entwickelt und mit den Mandatsträgern der beteiligten Fachgesellschaften und Organisationen abgestimmt.Empfehlungen Für die tägliche Optimierung der Versorgung von Patientinnen mit Vaginalkarzinom gilt: 1. Beachtung des Ausbreitungsmusters. 2. Einhaltung der abgestuften Diagnostik in Abhängigkeit vom Ausgangsstadium. 3. Wenn möglich Einsatz des Sentinel-Verfahrens im Rahmen eines individualisierten klinisch-therapeutischen Managements der Vaginalkarzinome. 4. Teilnahme an der Registerstudie zum Vaginalkarzinom.
Keywords: vaginal cancer; VaIN; sentinel lymph node biopsy